Leadership for engineers - Bennett, Ronald J.
In Leadership for Engineers: The Magic of Mindset, the authors share stories of emerging leaders and their experiences, as well as some critical information and tools that help you, as a student or technical professional, reflect on your experience and decide what comes next. Every student has untapped leadership abilities. This book helps them find and develop their inner leader, become the person he or she wants to be, and pursue their passions in ways that are productive and rewarding for themselves and others. This book identifies some common myths about leadership in technical fields, and then helps students identify their own leadership skills in the face of false assumptions. The authors show students how to make a real difference and explain why the world needs every student's best professional self. Each of the four parts of Leadership for Engineers includes four chapters comprised of testimonies from emerging leaders, as well as reflective questions at the end of each chapter. Reading through the scenarios and working through the questions will prepare you to lead in your career and your life